Starspots on Young Solar-Type Stars. Issue Volume 9:Issue S302(2013) (7th August 2014) - Brown, Carolyn; Carter, Brad; Marsden, Stephen; Waite, Ian
Abstract: Doppler Imaging of starspots on young solar analogues is a way to investigate the early history of solar magnetic activity by proxy. Doppler images of young G-dwarfs have yielded the presence of large polar spots, extending to moderate latitudes, along with measurements of the surface differential rotation. The differential rotation measurement for one star (RX J0850.1-7554) suggests it is possibly the first example of a young G-type dwarf whose surface rotates as almost a solid body, in marked contrast to the differential rotation of other rapidly rotating young G-dwarfs and the present-day Sun. Overall, our Doppler imaging results show that the young Sun possessed a fundamentally different dynamo to today.